2005
DOI: 10.1038/sj.gt.3302494
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenovirus-specific cytotoxic T lymphocyte response occurs after viral clearance and liver enzyme elevation

Abstract: The virus-specific cytotoxic T lymphocyte (CTL) response is a major obstacle to effective delivery of adenovirus gene therapy. However, its relative role in viral clearance, transgene elimination and hepatotoxicity remains unclear. In this paper, we present an analysis of viral clearance and liver toxicity in relation to the induction of the virus-specific CD8 T-cell response revealed by an MHC class I tetramer. A surprisingly high number of tetramer + CD8 T cells were found in the liver and lung and reached p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We measured cytokine expression on total T cell subpopulations, since a previous report has shown that most of the CD4 + and CD8 + T cells are virus-specific during the Ad infection (49). Our data suggest to us that IL-33 drove robust CD8 + and CD4 + T cells responses in the liver, which induced equally strong type-1 cytokine (IL-2 and IFN-γ) as well as type 2 cytokines (IL-4, IL-5, IL-6 and IL-13) in the liver and serum (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We measured cytokine expression on total T cell subpopulations, since a previous report has shown that most of the CD4 + and CD8 + T cells are virus-specific during the Ad infection (49). Our data suggest to us that IL-33 drove robust CD8 + and CD4 + T cells responses in the liver, which induced equally strong type-1 cytokine (IL-2 and IFN-γ) as well as type 2 cytokines (IL-4, IL-5, IL-6 and IL-13) in the liver and serum (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, "lymphocytopenia" in blood could reflect redistribution of cells to tissues where they are needed for mounting an immune response, and could in fact constitute a surrogate for immunological activity, as reported in mice or in humans treated with another immunotherapeutic. [34][35][36] When measuring lymphocytes 3 weeks later they are normally back to pretreatment values [25][26]33 but this was not the case with Ad3-hTERT-E1A-treated patients that had received previous Ad5 treatments (Figure 1a). These patients had some T-cells reactive against Ad3-hTERT-E1A already before treatment, but the median amount in blood did not change after the treatment (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of cells was examined by standard flow cytometry procedures as previously described (Chen et al, 2005). This involved six-color immunofluorescence staining of cell samples using a combination of FITC-, PE-, APC-, pacific-blue, PE-Cy7, and APC-Cy7 conjugated antibodies for anti-CD8, anti-CD28, anti-CD95, anti-CD45RO, anti-CD45RA, and anti-CD127.…”
Section: Methodsmentioning
confidence: 99%